2013
DOI: 10.1136/bmjquality.u660.w502
|View full text |Cite
|
Sign up to set email alerts
|

The F.R.I.D.A.Y.S. checklist - Preparing our patients for a safe weekend

Abstract: There is a higher incidence of mortality and adverse events among inpatients in UK hospitals at the weekend compared to weekdays. The high volume of routine tasks handed over by the weekday doctors on Fridays may be a contributing factor.An audit was carried out on four acute wards on a Friday evening at University Hospital Lewisham (UHL). It demonstrated that most patients had at least one outstanding task that would need completing by the on-call team over the weekend. To address this problem a concise and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The simplicity of the checklist made it possible for the staff to reduce the number of routine tasks for the weekend. 8 As with our problem, the study showed how routine tasks can continue on the weekend, just as our routine tasks continue during the evening and night.…”
Section: Introductionmentioning
confidence: 84%
“…The simplicity of the checklist made it possible for the staff to reduce the number of routine tasks for the weekend. 8 As with our problem, the study showed how routine tasks can continue on the weekend, just as our routine tasks continue during the evening and night.…”
Section: Introductionmentioning
confidence: 84%
“…Previous quality improvement (QI) projects, looking at handovers, trialled several systems, such as paper lists, proformas, stickers for insertion into notes and computer-based tools (Din et al, 2012;Ashton, 2014;Bethune et al, 2014;Jardine et al, 2014;Raptis et al, 2009;Govier and Medcalf, 2012;Palmer et al, 2014). These systems have strengths and weaknesses.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated the use of an electronic weekend handover in helping to improve patient safety and continuity of care. [6][7][8][9] The RCP identified a handover as "a major cause of preventable harm" and this forms the fundamental basis for this project. 4 …”
Section: Introductionmentioning
confidence: 99%